2019
DOI: 10.1111/jre.12665
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid slows down collagen membrane degradation in uncontrolled diabetic rats

Abstract: Aim To examine the in vitro biokinetics of hyaluronic acid (HA) from a collagen membrane (CM) and to evaluate the in vivo effect of immersion of the CM in HA solution on its degradation in streptozotocin (STZ)‐induced diabetes conditions in a rat calvaria subcutaneous model. Background CM degradation is accelerated in uncontrolled diabetic rats. Immersion of CM in HA has been suggested to decrease their resorption rate without interfering with their tissue integration and structural degradation. However, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
5
26
0
Order By: Relevance
“…[26][27][28][29] In support of our contention that DM results in enhancement of inflammation/collagenolysis around the membranes, we found that immersion of the membranes in tetracycline (TC) or hyaluronic acid (HA) prior to implantation mitigated their resorption in diabetic rats, probably because of the anticollagenolytic/anti-inflammatory properties, respectively, of these additives. [26][27][28][29] Therefore, the present study was performed to compare the local expression and production of several pro-inflammatory molecules at the membrane implantation site between diabetic and normoglycemic rats and provide a better understanding of the molecules that drive the exaggerated inflammation shown histologically in and around the membranes. We analyzed the presence of IL-6, TNF , MMP-9, MIP-1 , MIP-2 , and MIF, representing different aspects of the inflammatory process, namely cytokines, chemokines, and MMPs.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…[26][27][28][29] In support of our contention that DM results in enhancement of inflammation/collagenolysis around the membranes, we found that immersion of the membranes in tetracycline (TC) or hyaluronic acid (HA) prior to implantation mitigated their resorption in diabetic rats, probably because of the anticollagenolytic/anti-inflammatory properties, respectively, of these additives. [26][27][28][29] Therefore, the present study was performed to compare the local expression and production of several pro-inflammatory molecules at the membrane implantation site between diabetic and normoglycemic rats and provide a better understanding of the molecules that drive the exaggerated inflammation shown histologically in and around the membranes. We analyzed the presence of IL-6, TNF , MMP-9, MIP-1 , MIP-2 , and MIF, representing different aspects of the inflammatory process, namely cytokines, chemokines, and MMPs.…”
supporting
confidence: 54%
“…These time points were selected based on our previous studies showing accelerated membrane resorption in this model. [26][27][28][29] Dermal tissues were dissected away leaving the periosteum undisturbed and the membrane including overlying and underlying tissues was retrieved. Six samples from each group were immediately frozen in liquid nitrogen and then transferred to −80 • C for RNA/protein isolation.…”
Section: Surgery and Tissue Handlingmentioning
confidence: 99%
See 3 more Smart Citations